2014
DOI: 10.1111/cge.12442
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel mutations in the VPS33B gene involved in arthrogryposis, renal dysfunction, and cholestasis syndrome

Abstract: Arthrogryposis, renal dysfunction, and cholestasis (ARC) syndrome is an autosomal recessive disorder caused by mutations in the VPS33B and VIPAS39. Here, we report novel mutations identified in four patients with ARC syndrome. We analyzed the entire coding regions of the VPS33B and VIPAS39 genes by direct sequencing. To detect novel splice site mutations, mRNA transcripts were analyzed by reverse transcription-polymerase chain reaction (RT-PCR) and sequencing. All four patients had compound heterozygous varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Our study demonstrates that the cause of death for Vps33B flies is not the bacterial load itself but exaggerated anti-microbial responses to non-pathogenic microbes, similar to sepsis that contributes to death in ARC patients (Jang et al, 2009; Seo et al, 2014). Furthermore, such exaggerated TLR signaling can cause innate immune paralysis (Hotchkiss et al, 2013), where the innate immune system, following a robust response to the first infection, fails to respond to secondary infections, possibly resulting in enhanced susceptibility of ARC patients to pathogenic microbes.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Our study demonstrates that the cause of death for Vps33B flies is not the bacterial load itself but exaggerated anti-microbial responses to non-pathogenic microbes, similar to sepsis that contributes to death in ARC patients (Jang et al, 2009; Seo et al, 2014). Furthermore, such exaggerated TLR signaling can cause innate immune paralysis (Hotchkiss et al, 2013), where the innate immune system, following a robust response to the first infection, fails to respond to secondary infections, possibly resulting in enhanced susceptibility of ARC patients to pathogenic microbes.…”
Section: Discussionmentioning
confidence: 81%
“…Persistent infections and sepsis are recurring symptoms in ARC patients (Jang et al, 2009; Seo et al, 2014). Our findings indicate that, rather than being an indirect consequence of failures in other organ systems, these complications could reflect direct roles of the ARC protein Vps33B in innate immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vacuolar protein sorting 33B (VPS33B) is a late endosome‐ and lysosome‐associated protein in the Sec‐1 domain family, and it plays an important role in the segregation of intracellular molecules into distinct organelles. Mutation of VPS33B is linked with arthrogryposis, renal dysfunction and cholestasis (ARC) syndrome, which is a rare autosomal recessive disease involving multiple systemic disorders . VPS33B is required for megakaryocyte biogenesis, platelet activation and in vivo thrombosis and homeostasis .…”
Section: Introductionmentioning
confidence: 99%
“…Mutation of VPS33B is linked with arthrogryposis, renal dysfunction and cholestasis (ARC) syndrome, which is a rare autosomal recessive disease involving multiple systemic disorders. 2,3 VPS33B is required for megakaryocyte biogenesis, platelet activation and in vivo thrombosis and homeostasis. 4,5 In tumors, only one study has found that VPS33B serves as an important tumor suppressor in hepatocarcinogenesis.…”
Section: Introductionmentioning
confidence: 99%